Public Transport Service Provisions and Policy Implications for Columbarium Trips - W.Y. Szeto; S. Sun; R.C.P. Wong (International Journal of Transportation Science and Technology, 2015)
Grave-sweeping is one of the popular special events in Asian cities, especially in Chinese societies, in which families express filial piety to their ancestors during two traditional grave-sweeping festivals in a year. The extraordinary high travel demand is often attracted to columbaria within a relative short period around the festivals, and induces severe impacts to the local traffic. It is challenging for the government and private operators to formulate a public transport service setting to satisfactorily cater all the visitors' travel demand. This paper aims to propose an optimization framework to identify the optimal provisions of public transport services for columbarium trips to achieve consumer surplus or profit maximization. Numerical studies are carried out using the travel demand data collected from a selected columbarium, to examine the effects of different public transport service settings to the policy objectives in various cases. The model results show that the current situation is neither consumer surplus nor profit optimum. Improvement schemes are suggested in relation to allow various fares during different visit periods and provide multiple public transport feeder services to serve the visitors during the high travel demand period.